Utilizing Suggestopedia Method in Teaching English Grammar - Sa'diyah, Siti Halimatus; Rozi, Fathor; lestari, Wahyu (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to analyze and examine the use of the suggestopedia method in teaching English Grammar as one of the primary methods for understanding Grammar material. The research method used is a descriptive qualitative approach with the type of case study. The research location is in the Al Hamidiyah area of the Nurul Jadid Islamic boarding school student cottage and for research subject in special classes for student linguistics including two language teachers as primary informant subject and one student as secondry informants subject. Meanwhile, the data collection used in this study included direct observation and unstructured interviews in determining the data's accuracy. The data analysis technique consists of the stages of collecting data, preparing it for analysis, analyzing it, and then concluding the analysis. The results obtained from the application of the suggestopedia method are the increasing understanding of students in participating in Grammar lessons because students are invited to understand the core of the material in an enjoyable and calming way, namely by good class arrangement and being given soothing music accompaniment. The implication is that students' understanding of learning can be achieved with variations in the learning carried out by the teacher so that students do not feel anxious and enjoy themselves in class.